Frequency Regulation of AUT Microgrid Using Modified Fuzzy PI Controller for Flywheel Energy Storage System - mohammad saeed mahdavi; Gevork B. Gharehpetian; Parisa Ranjbaran; Hossein Azizi (AUT Journal of Electrical Engineering)
Usage of flywheel energy storage system (FESS) is a common method for frequency regulation due to its high power injection capacity and long life time. FESS is equipped by two back-to-back inverters including grid-side inverter and machine-side inverter. In conventional method, the machine-side inverter sets the active power and machine flux while grid-side inverter sets the reactive power and common DC bus voltage by conventional PI current controllers. Especially for frequency regulation, FESS is constantly faced with change of power and operating point but PI controller performance is dependent on operating point of the system. In this paper, at first, the control of both active and reactive power is moved to grid-side inverter and control of DC bus voltage and machine flux is moved to machine-side inverter. Then a modified version of fuzzy PI controller is proposed for grid-side inverter control in which rated PI controller coefficients values are optimally designed for rated operating point by feed-back linearization and pole placement then fuzzy system (FS) is used for PI coefficients variation around the rated values when operating point changes. Experimental results verify the performance of the proposed FESS control system for AUT microgrid frequency regulation and also moving the DC bus voltage control to machine-side inverter.